A Pilot Study of a Physical Therapy Cadaveric Anatomy Course: Assessing the Impact of Examination Format on the Learning Environment. Issue 3 (23rd September 2020) - Fournier, Dale E.; Groh, Adam M. R.
Abstract : Anatomy education continues to evolve in health professional programs as curricula shift to competency‐based models and contact hours decrease. These changes in curricula may significantly alter the learning environment for students. Importantly, changes in learning environment have been shown to impact student learning strategies and well‐being. It follows, then, that an investigation of students' perceptions of the learning environment is key to understand the impact of modern anatomy curriculum alterations. The current pilot study evaluated the impact of modifying examination format on the learning environment of physical therapy students participating in a human cadaveric anatomy course. Two study cohorts of first year (entry‐level) physical therapy students were invited to complete a preliminary learning environment questionnaire with 13 visual analog scale items and four short answer items. One study cohort was tested with a viva (oral) practical examination, and the other, with a bell‐ringer practical examination. Analysis of quantitative items revealed two significant findings: physical therapy students in the bell‐ringer cohort found it was more difficult to prepare for their examination, and that they had inadequate time to respond to questions compared to the viva cohort. Analysis of qualitative items revealed distinct themes that concerned physical therapy student learning environment specific to cadaveric anatomy. These results demonstrate that examination format can influence the learning environment of physical therapy students studying cadaveric anatomy. As a result, care needs to be taken to ensure that modernized curricula align the examination format to the method of instruction and the future application of students' knowledge in clinical practice.